2017
DOI: 10.1016/j.je.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness and completeness of measles vaccination among children in rural areas of Guangxi, China: A stratified three-stage cluster survey

Abstract: BackgroundLarge-scale outbreaks of measles occurred in 2013 and 2014 in rural Guangxi, a region in Southwest China with high coverage for measles-containing vaccine (MCV). This study aimed to estimate the timely vaccination coverage, the timely-and-complete vaccination coverage, and the median delay period for MCV among children aged 18–54 months in rural Guangxi.MethodsBased on quartiles of measles incidence during 2011–2013, a stratified three-stage cluster survey was conducted from June through August 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Migrant mothers were found as a positive factor of recall bias for DTP and MCV. Generally, migrant status had been considered as a risk factor of low coverage, poor completeness and timeliness of childhood vaccination in several previous surveys in Zhejiang Province and other areas of China [28,29,30]. Commonly, migrant people have poor social adaptation ability, which is reflected in challenges such as adapting to a new socio-cultural environment or living in poor economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Migrant mothers were found as a positive factor of recall bias for DTP and MCV. Generally, migrant status had been considered as a risk factor of low coverage, poor completeness and timeliness of childhood vaccination in several previous surveys in Zhejiang Province and other areas of China [28,29,30]. Commonly, migrant people have poor social adaptation ability, which is reflected in challenges such as adapting to a new socio-cultural environment or living in poor economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, a study conducted in Sri Lanka found higher timeliness in rural areas compared to urban settings [ 5 ]. The education of the mother has also been shown in other studies [ 2 , 4 , 44 ] to be an important driver on timely immunization or timely completion of specific vaccinations. These results indicate that there is a need to further improve access to health services, especially in remote rural areas.…”
Section: Discussionmentioning
confidence: 80%
“…The timely administration of vaccines is considered to be important for both individual and community immunity. Studies in the UK [ 1 ], China [ 2 ], the USA [ 3 ] and lower-income countries such as Senegal [ 4 ], Sri Lanka [ 5 ], Malawi [ 6 ] and India [ 7 , 8 ] have investigated the impact of timeliness on vaccination. Delayed vaccinations of children may increase the risk of infection before vaccination, compromising the success of the intervention as well as herd immunity.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Thus, the regional differences in proportions of parental migration may impact the heterogeneity of vaccination timeliness in this area, which can further cause the variation in measles incidence. [1] In general, it seems that the measles immunization program was unevenly carried out in Ludian county, there were vulnerable populations in the mountainous areas. These findings highlight the necessity to further optimize vaccination policies and measures in rural China so as to reduce inequities in timely vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Measles is a highly contagious disease and one of the major causes of death among children worldwide. [1] The average incubation period of measles is 10 days. [2] The main clinical symptoms are fever, cough, coryza (running nose), red maculopapular rash, Koplik spots, anorexia, diarrhea (especially in infants), and generalized lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%